Principles of Agnikarma and its Advances for Shonitsthapana (Hemostasis) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Agnikarma has been one of the peculiar parasurgical procedures described in Sushrut Samhita. The mostimportant indication of Agnikarma is when there is bleeding from vessel or diseases in which bleeding isexpected. Technology and instruments used for hemostasis now a days differ from ancient ones. Howeverfundamental principle of heating the tissues remains same which is widely used in present era. Earlier rods(shalaka) made from different metals were used for burning out bleeding veins. Red hot shalaka was appliedon tissues and bleeders so that contraction of vessels occurs. So hemostasis was achieved by cauterization oftissues at high temperature. With advancement of technology in bio-medical engineering various machineslike Electrocautery, Infrared coagulation, Electrosurgical unit (high frequency and low frequency) andLASERs were invented for similar purpose.In Electrocautery electrical current is used to heat a metal wire to burn or coagulate the specific areaof tissue. In Electrosurgical unit alternating current is passed through tissue and heat is created by theresistance of tissue to current. Electrodes are used to cut, coagulate or even fuse the tissue. IRC involvesthe use of infrared light as a heat source to coagulate vessels supplying blood. Lasers are used to ablate theveins in which amplified light energy is used to generate heat. Tissue dehydration, protein coagulation andvaporization are the processes involved in achieving hemostasis.Working principles and energy sources used in these devices vary from each other; however the hemostasisis achieved by common fundamental principle i.e. generating heat which is similar to Agnikarma.
Keywords: Agnikarma, Hemostasis, Electrocautery, Lasers, BEIM